The effect of nutrition counselling on knowledge and blood sugar level of diabetes mellitus patients - Yulia Fitri; Abdul Hadi (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Untreated hyperglycemia in diabetes mellitus (DM) patients will worsen the patient's condition and can lead to serious complications. Nutritional counselling related to the DM diet is an important step that can motivate changes in diet and lifestyle to improve blood glucose control. Objective: The purpose of this study was to determine the provision of nutritional counselling on the level of knowledge and fasting blood sugar levels of outpatients with DM at the Darul Imarah Community Health Centre. Methods: The research used a quasi-experimental, one-group pre-test-post-test design with 36 DM patients at the Darul Imarah Community Health Centre. Nutritional counselling used a leaflet, the level of knowledge was measured using a questionnaire and fasting blood sugar levels were measured using the Easy Touch GCU and re-measured (post-test) after 1 month of intervention. Statistical tests used the Wilcoxon test with a significance level of p < 0.05. Results: The results showed an increase in knowledge scores from 60 (IQR: 40-60) to 80 (IQR: 60-80) with a large effect size (r=0.81). Furthermore, the results showed a decrease in the median fasting blood glucose from 200 (IQR: 180-207.5) mg/dL to 180 (IQR: 170-200) mg/dL with a large effect size (r=0.65). There were differences in knowledge levels (Z = -4.87; p < 0.001) and fasting blood glucose (Z = -3.91; p < 0.001) before and after nutritional counselling. Conclusion: The conclusion of this study is that nutrition counselling using leaflets is effective in increasing knowledge and reducing blood glucose levels.